Real-time tidal data transfer for depth correction using radio link [electronic resource] - 374032 Mohd. Hilmi Abdullah (Skudai : Universiti Teknologi Malaysia, 2008)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik)) - Universiti Teknologi Malaysia, 2008